Clinicopathological aspects and their relation to prognosis in adult-type granulosa cell tumor of the ovary Aspectos clinicopatológicos e sua relação com o prognóstico em tumor de células da granulosa do tipo adulto do ovário - Maurício De Angelo Andrade; Joyce de Brito Pupo; Sophie Derchain; Liliana Aparecida Lucci De Angelo Andrade (Jornal Brasileiro de Patologia e Medicina Laboratorial, 2009)
INTRODUCTION AND OBJECTIVE: The adult granulosa cell tumors (AGCT) correspond to less than 5% of ovarian neoplasias. They are considered low malignant potential tumors and may recur after many years. The differential diagnosis must be made with other primary or metastatic ovarian neoplasias. The aim was to analyze clinical and pathological aspects of AGCT and relate them to its evolution. METHOD: in a 10- year (1995-2004) review of the files from University of Campinas Clinical Hospital, Brazil, 20 AGCT cases were found. The clinical records and slides were reviewed and age, symptoms, macro and microscopic aspects, diagnostic staging and recurrence were considered. When there was intraoperative biopsy, its accuracy was evaluated. RESULTS: Age ranged from 27 to 79 years (mean: 53) and the follow-up from 12 to 96 months (mean: 42). The main symptoms were post-menopause bleeding (45%), abdominal pain (35%) and palpable mass (25%). Most tumors were yellowish (60%) and the solid aspect (40%) was more common than the cystic or solid-cystic. The histological patterns were 40% solid, 15% macrofollicular and 45% combined forms. All of them with low mitotic index. Only three out of nine intraoperative frozen sections were accurately diagnosed. The clinical staging was 13 cases in Ia (65%), one case Ic and 6 IIIc. In three out of 14 hysterectomies there was simple endometrial hyperplasia with no atypia. Only the disease staging was significantly associated with recurrence (p < 0.0001). CONCLUSION: ACGT generally occurs after menopause and intraoperative biopsies are commonly inconclusive. Only advanced staging was related to the worst prognosis. INTRODUÇÃO E OBJETIVO: O tumor de células da granulosa tipo adulto (TCGA) corresponde a menos de 5% das neoplasias ovarianas. São de baixo potencial de malignidade, podem recorrer depois de muitos anos, e o diferencial deve ser feito com outras neoplasias primárias ou metastáticas. Analisamos os aspectos clínicos e patológicos do tumor, relacionando-os à evolução. MÉTODOS: Na revisão de 10 anos dos arquivos do laboratório de Anatomia Patológica do Hospital das Clínicas da Universidade de Campinas (UNICAMP), 20 casos de TCGA foram encontrados. Os prontuários e as lâminas foram revisados e considerados: idade, sintomas, aspectos macro e microscópicos, estádio ao diagnóstico e à recidiva. Quando houve biópsia intraoperatória, sua acurácia foi avaliada. RESULTADOS: A idade variou de 27 a 79 anos (média: 53); o seguimento de 12 a 96 meses (média: 42). Os sintomas principais: sangramento pós-menopausa (45%), dor abdominal (35%) e massa palpável (25%). A maioria era amarelada (60%), o aspecto sólido mais comum (40%) que o cístico ou sólido-cístico. Os padrões histológicos foram: 40% sólido, 15% macrofolicular e 45% de formas combinadas, todos com baixo índice mitótico. Apenas três de nove casos submetidos à biópsia intraoperatória foram diagnosticados corretamente. O estádio clínico foi: 13 casos Ia (65%), um caso Ic e seis, IIIc. Em três de 14 histerectomias analisadas, havia hiperplasia endometrial simples sem atipia. Apenas o estádio da doença foi significativamente associado à recidiva (p < 0,0001). CONCLUSÃO: TCGA geralmente ocorre após a menopausa, as biópsias intraoperatórias são mais comumente inconclusivas e apenas o estádio avançado esteve relacionado com o pior prognóstico.